Development of wireless vibration sensor for condition monitoring of electrical machines - Chua, Wang An (2017)
Electrical machines have widespread applications in domestic and industrial sectors. These machines are either operated independently or as part of a larger process to accomplish a number of objectives. By introducing active monitoring of the relevant fault signatures, the faults can be detected at an early stage before any catastrophic failures or breakdowns of the electrical machines can happen. This would result in an increase in productivity, and an overall decrease in the operational cost of the electrical machines. The electrical machine and signature considered in this project is an induction motor and its vibration signature respectively. The application of wireless sensor was explored for testing of new applications in the field of wireless process automation, which in the past were limited by economic and technological barriers. This report presents the development of wireless vibration sensor, specifically mountable onto the shaft of an induction motor. The development covers the design and fabrication of the Printed Circuit Board (PCB) hardware, wireless sensor network firmware and a Graphical User Interface (GUI) software that provides a logging and storing of data obtained from the wireless vibration sensor. The developed wireless sensor was deployed on an induction motor test rig and the vibration signatures were obtained. The signatures obtained were then processed using Fast Fourier Transform (FFT) in MATLAB for validation of the wireless vibration sensor which could be used for further study of fault detection in the induction motor.